Impact of Various Performance Parameters on Distributed Protocols in Wireless Sensor Networks - Kaur, Sukhkirandeep; Mir, RN (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Network (WSN) consists of small sensor nodes that cooperate with each other to send sensed data to the Base-Station (BS). Several challenges are imposed in WSN with energy consumption being the most important. Clustering improves energy efficiency in WSN by sending data through CHs in one-hop and multi-hop communication. Distributed clustering methods are more efficient as compared to centralized clustering methods in terms of energy efficiency and the choice of the optimal parameter value is important in distributed clustering as it acts as a significant part in preserving energy. Individual parameters like the position of BS, the optimal number of CHs, heterogeneity factor etc. impact the performance in distributed protocols. This work evaluates the performance of well-known distributed protocols by varying the values of different parameters to study their effect on network performance. Simulations are performed and results are analyzed to check the effect of performance parameters.